Energy Efficient LEACH (EE-LEACH) Routing Algorithm for Wireless Sensor Networks - Pillay, Kosheila Sundram (Universiti Malaysia Sarawak (UNIMAS), 2019)
A wireless sensor network (WSN) consists of a group of sensor nodes which communicate changes in the environment to a base station. Due to the limited power resource of the nodes, frequent node failure can lead to a drastically shorter lifetime of WSNs. Low energy adaptive clustering hierarchy (LEACH) routing protocol was developed to provide better energy efficiency in WSN due to its structural organization. However, it does not guarantee a balanced selection of cluster heads (CHs) and equal cluster size, resulting in an imbalanced load distribution among the CHs. Furthermore, re-election of CHs and re-clustering in each round increase network energy consumption, further decreasing the lifetime of WSNs. Therefore, this research work proposes an energy-efficient LEACH (EE-LEACH) algorithm to elect CHs based on residual energy, RSSI, and random probability to distribute the load evenly among the CHs. Nodes with higher residual energy and RSSI than the threshold are selected as the CHs which continue operating as CHs until their residual energy is lower than the threshold. This reduces the re-election and re-clustering processes which lowers the network energy consumption. An extensive simulation via NS-2.34 reveals that EE-LEACH shows about 25.49% and 15.58% improvement in network lifetime and energy consumption, respectively, compared to LEACH. The results also show that EE-LEACH transmits about 51% more data than LEACH. From the improved results, it can be concluded that the proposed EE-LEACH algorithm performs much better in WSNs while reducing the average energy consumption and packet loss ratio.